A Comparison of the Mechanical and Sensory Properties of Baked and Extruded Confectionery Products - Butt,S; Charalambides,M; Mohammed,IK; Powell,H (AIP Publishing, 2017)
Traditional baking is the most common way of producing confectionery wafers, however over the past few decades, the extrusion process has become an increasingly important food manufacturing method and is commonly used in the manufacturing of breakfast cereals and filled snack products. This study aims to characterise products made via each of these manufacturing processes in order to understand the important parameters involved in the resulting texture of confectionery products such as wafers. Both of the named processes result in brittle, cellular foams comprising of cell walls and cell pores which may contain some of the confectionery filling. The mechanical response of the cell wall material and the geometry of the products influence the consumer perception and preference. X-Ray micro tomography (XRT) was used to generate geometry of the microstructure which was then fed to Finite Element (FE) for numerical analysis on both products. The FE models were used to determine properties such as solid modulus of the cell walls, Young’s modulus of the entire foam and to investigate and compare the microstructural damage of baked wafers and extruded products. A sensory analysis study was performed on both products by a qualified sensory panel. The results of this study were then used to draw links between the mechanical behaviour and sensory perception of a consumer. The extruded product was found to be made up of a stiffer solid material and had a higher compressive modulus and fracture stress when compared to the baked wafer. The sensory panel observed textural differences between the baked and extruded products which were also found in the differences of the mechanical properties of the two products.